Purification of Fungul Glucoamylase and Study the Effect of Concentration And Thermal Processing on Enzymatic Activity of Starch Hydrolysis - Jwaid, M. K. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Glucoamylase from black Aspergillus niger isolate was purified by ammonium sulfate precipitation and sephadex G 200 filtration. A trial for the purification of glucoamylase resulted in an enzyme with a specific activity of 6472 unit/mg protein with 10 times fold. The main goal of the present work was to test this enzyme in hydrolyzing the raw starch. Two substrates were used: corn starch and potato starch 2% (w/v). The effect of enzyme dosage and thermal processing of substrate on kinetics and efficiency of hydrolysis were studied. The results suggested that the glucoamylase activity is increased as the increase of enzyme concentration and the enzyme was sufficiently effective in hydrolyzing tested raw starch, and thermal modification of substrates was not necessary.